Case Report: Intercostal Lymph Node Metastasis: A Case Report and Review of the Literature - Zhou, Yurong; Hou, Jinxuan; Meng, Ning; Daniel, Staiculescu; Chen, Jiang; Xu, Liying (Frontiers in Oncology, 2021)
The axillary lymph nodes are the primary group responsible for breast lymphatic drainage and, consequently, are the most common location for breast cancer metastasis. However, lymphatic pathways running from the breast, via intercostal spaces, to parasternal lymph vessels have also been identified. According to the American Joint Committee on Cancer eighth edition manual, the regional lymph node metastasis normally travels to the ipsilateral axillary, supraclavicular, subclavicular, and internal mammary lymph nodes, but the presence of intercostal metastasis is out the range of these regional lymph nodes. Intercostal lymph node metastasis of breast cancer is an extremely rare extra-axillary site, little of which has been reported in literature. Despite its rarity, it has the capacity to adversely affect prognosis of breast cancer and drastically influence treatment choice. Here, we analyze such a case, with a changed surgical approach of radical mastectomy and metastatic intercostal lymph node dissection due to the presence of intercostal lymph node metastasis indicated via MRI. Furthermore, the potential application of preoperative 3-dimensions (3D) visualization and surgical planning is discussed.